Introduction to Industrial Engineering - Boardman, Bonnie; Open Textbook Library (Open Textbook Library, 2020)
This book was created for an undergraduate Introduction to Industrial Engineering course at The University of Texas at Arlington (UTA). The chapters give an overview of the profession and an introduction to some of the tools used by industrial engineers in industry. There are interactive content exercises included at the end of most chapters. This interactive content aims to engage students in the content as they are reading. The book will continue to revised and updated with new information as it becomes necessary.
1. What is Industrial Engineering? -- 2. Teamwork -- 3. What is Problem Solving? -- 4. Big Ideas in Industrial Engineering -- 5. Using Models -- 6. Deming's 14 Points -- 7. People in the System -- 8. Systems Thinking -- 9. Lean Operations -- 10. The IE Approach -- 11. Organizations' Missions, Visions, and Values -- 12. Lifelong Learning
In English.
Description based on print resource
Keywords: Engineering -- Textbooks